Application of the Defensive Training Model in Volleyball Games at the Putra Jatitujuh Club - Alvarizi, Rudi; Sahudi, Udi; Yudha, Brio Alfatihah Rama (Universitas Majalengka, 2023)
The Jatitujuh Men's Team's defense against attacks from the opposition was extremely poor; in two sets of games, the Block on Target was only 25 times, while the Block Out Target was 30 times. Poor defense is caused by players not communicating with one another, defending in an unprepared manner when attacked, continuing to jump incorrectly, and having both hands wide. To get around this, a defensive training paradigm was selected. The purpose of this study is to ascertain whether defensive training models have an impact on a player's capacity to fend off attacks from opponents during a volleyball match. Quasi Experimental Design research, specifically One-Group Pretest-Posttest Design, is the methodology employed in this study. There were 14 members of the Putra Jatitujuh Club who made up the population of this study. A saturated sample was used, meaning that every member of the population was included in the sample. The study's findings indicate that defensive training models have an impact on players' capacity to fend off opponents' attacks during volleyball matches. The results of the t test show that, at the 5% significance level, with df=n-1=14-1=13, or 2.160, the tcount value of 3.576 is greater than the ttable value. As a result, Ho is rejected and Ha is accepted, indicating a significant difference in the ability to withstand an opponent's attack before and after receiving treatment in the form of a defensive training model and the defensive training model has an influence of 51.6% in increasing the ability to withstand an opponent's attack in a volleyball game.